Self Compassion Dan Subjective Well Being Pada Sandwich Generation Yang Bekerja - Anggraini, Dewi; Putridinanti, Naurah Demi; Amalia Juniarly (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
The "sandwich generation" refers to working-age individuals responsible for the financial support of extended family members such as parents, grandparents, or siblings in addition to their own nuclear families. This demographic often faces significant conflict due to financial strain, which can negatively impact their quality of life, job satisfaction, and overall subjective well-being. This study investigates the relationship between self-compassion and subjective well-being among the sandwich generation in Indonesia. Utilizing a quantitative approach, the study sampled 134 working individuals aged 20–60 who provide multi-generational financial support; an additional 50 participants with identical characteristics were included for the pilot study. Data analysis included normality and linearity assumption tests followed by hypothesis testing. The results indicate a significant positive relationship between self-compassion and subjective well-being (p < 0.05). Findings reveal that self-compassion accounts for an 80.2% effective contribution to subjective well-being, suggesting that the remaining 19.8% is influenced by external factors not covered in this study. These results highlight the critical role of self-compassion in maintaining mental health for those navigating multi-generational caregiving demands. Keywords: Self-Compassion; Subjective Well-Being; Sandwich Generation.